Compressive behavior of built-up closed box section columns consisting of two cold-formed steel channels. (June 2020) - Nie, Shao-Feng; Zhou, Tian-Hua; Zhang, Yang; Liu, Bo
Abstract: Thirty specimens of built-up closed box sections consisting of two cold-formed steel channels of various cross sections (B92 and B143), lengths (3000, 1500, 450, and 270 mm), and thicknesses (1.2 and 1.5 mm) were tested subject to concentric and eccentric axial compression. Failure modes were analyzed and load vs. displacement curves were obtained. The test results indicate that the failure modes of long and medium columns subject to concentric axial compression are flexural buckling about the weak axis, whereas that of the short column is excessive local buckling; specimens subject to eccentric axial compression about the strong and weak axes exhibited flexural-torsional buckling and flexural buckling, respectively. Finite element (FE) models were established and verified. Detailed parameter studies were performed to evaluate the accuracy of code equations for a wide range of parameters. The FE analysis results indicate that the concentric axial compression strength of the columns decreased with an increase in the slenderness ratio of column or the web height-to-thickness ratio; increasing the flange width can significantly increase the stability and strength of the column; the eccentric axial compression strength of the column about the weak axis decreased faster than that about the strong axis. Finally, the effectiveness of the design methods, i.e., the effective ratio of width-to-thickness method in the Chinese code, effective width method, direct strength method, and load and resistance factor design in North American specifications to predict the strength of this type of built-up column is evaluated. For the B92 series columns and B143 series column with slenderness ratio of the column greater than 92, it is conservative to use design methods to calculate the concentric axial compression strength of the column. Additionally, it is conservative to use the design methods to calculate the eccentric axial compression strength of the columns. Highlights: Axial compression tests were conducted on built-up closed box section columns consisting of two cold-formed steel channels. The failure modes of the specimens were analyzed. FE models of built-up closed box section columns were developed and verified with test results. A parametric study was performed varying the screw spacing, the slenderness ratio of the columns, etc. The effectiveness of available design codes to predict the strength of built-up closed box section columns was evaluated.